2014
DOI: 10.1089/thy.2013.0688
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 3,5-Diiodothyronine in Sera of Patients with Altered Thyroid Status Using a New Monoclonal Antibody-Based Chemiluminescence Immunoassay

Abstract: The established CLIA is highly specific, sensitive, precise and accurate for 3,5-T2 detection in human serum. Because 3,5-T2 is not regulated in conditions of an altered thyroid state, it is most likely that serum 3,5-T2 concentrations are not directly dependent on feedback regulation via the hypothalamic-pituitary axis. In addition 3,5-T2 is present in thyroidectomized individuals on T4 substitution, and it is elevated after T4 substitution compared with healthy controls. We conclude that these data support e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 48 publications
5
57
1
2
Order By: Relevance
“…This finding is also in agreement with our previous study, where no correlation between 3,5-T2 and serum T4 and T3 concentrations was observed in healthy or T4-substituted individuals (20). However, since early experimental work suggested an extrathyroidal conversion of 3,5-T2 from T3 also in humans (45), the missing correlation observed within our tight subset does not necessarily exclude a physiological link between both, and further effort is needed for clarification.…”
Section: Figsupporting
confidence: 93%
See 4 more Smart Citations
“…This finding is also in agreement with our previous study, where no correlation between 3,5-T2 and serum T4 and T3 concentrations was observed in healthy or T4-substituted individuals (20). However, since early experimental work suggested an extrathyroidal conversion of 3,5-T2 from T3 also in humans (45), the missing correlation observed within our tight subset does not necessarily exclude a physiological link between both, and further effort is needed for clarification.…”
Section: Figsupporting
confidence: 93%
“…For this purpose, we used a newly developed immunoassay (20), representing the only currently available method to determine serum 3,5-T2 concentrations in humans (26)(27)(28). Our data revealed significant bell-shaped associations of serum 3,5-T2 concentrations with serum glucose concentration and TSH concentrations in the fasting state, pointing toward a versatile role of circulating 3,5-T2 in human metabolism.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations